Reception Of Umsida Students To “Umsida1912 Instagram” As A Media Of Information On Umsida Students 'Activities: Resepsi Mahasiswa Umsida Terhadap “Instagram Umsida1912” Sebagai Media Informasi Kegiatan Mahasiswa Umsida - Rama Bagus Satria; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2021)
Instagram can be used as a mass communication medium that can reach a wide audience in the digital world, and Instagram users can be categorized as active audiences to play a role in giving meaning to various accounts, especially official accounts at an organization / company / university. No exception the official account from UMSIDA (Muhammadiyah University of Sidoarjo). This account is expected to be a medium of communication between UMSIDA and UMSIDA students. The purpose of this study was to see Umsida Student Reception on